Analisis dan Evaluasi Sistem Absensi Karyawan pada Hotel AP Premier Batam - Pradino Kusumo; Muhammad Donal Mon (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
A hotel is a building with rooms that are rented out as a place to stay, event venue and place to eat. Batam has a fairly good hotel population because it directly borders Singapore. One of the hotels in Batam is the AP Premier Hotel, this hotel has four star status in Batam. The problem with this hotel is that the attendance system is often problematic, disrupting payroll at the end of the month. With these problems, the author proposes to create a manual attendance which aims to assist HRD in making payroll at the end of each month, using a direct implementation method. The results obtained from this activity are in the form of softcopy and hardcopy in the form of manual attendance which will be carried out at the hotel.